Paradigma Optimality Theory dalam Pembentukan Partisipel Aktif Verba Triliteral Bahasa Arab - Mardiah, Zaqiatul; Hizbullah, Nur; Rachman, Fazlur (Diwan: Jurnal Bahasa dan Sastra Arab, 2023)
The morphological process of Arabic active participles from strong and weak verbs was investigated using optimality theory in algorithm formulation. Wright (1996) and Wher (199)4 provided research data for this study. The study’s goal is to capture the input of triliteral verbs that can generate multiple outputs to form active participles with many constraints, as well as to formulate one-to-one form-meaning relations in every step of the morphological process to form active participles. The two objectives were completed for the purpose of developing an algorithm for an Arabic morphological computer programme. According to the findings of this study, the morphological rules of Arabic provide opportunities for violations, so that the output forms become the most optimal forms precisely because they violate these rules. In other words, because there are so many exceptions in the process of forming the active participle, developing a morphological model is difficult. However, OT provides the appropriate model to allow for the formulation of every single form of an existing participle. مستخلص قام هذا البحث بتحليل وصياغة العملية الصرفية لتكوين اسم الفاعل باللغة العربية المشتقة من الأفعال الثلاثية الصحيحة والأفعال المعتلة باستخدام نظرية المثلى (Optimaliy Theory-OT) المتعلقة بصياغة الخوارزمية. تم جمع بيانات البحث من Wright (1996) و Wher (1994). إن اهتمام الدراسة هو التقاط مدخلات الأفعال الثلاثية التي يمكن أن تولد عددًا من النواتج في تكوين اسم الفاعل مع عدد من القيود؛ ولصياغة علاقة معنى واحد لواحد في كل خطوة مفردة من العملية المورفولوجية لتكوين اسم الفاعل. وأوضحت نتائج هذه الدراسة أن القواعد الصرفية للغة العربية توفر فرصًا للانتهاك، بحيث تصبح صياغة النتائج هي الصياغة المثلى، على وجه التحديد لأنها تنتهك هذه القواعد. بعبارة أخرى، هناك العديد من الاستثناءات في عملية تكوين اسم الفاعل، لذا فإن صياغة نموذج صرفي ليس بالأمر السهل. ومع ذلك، تقدم نظرية المثلى النموذج الصحيح بحيث لا يزال من الممكن صياغة أي اسم الفاعل. الكلمات المفتاحية: نظرية المثلى؛ الفعل الصحيح؛ الفعل المعتل؛ الادخال-الإنتاج